Use of letermovir in off-label indications: Infectious Diseases Working Party of European Society of Blood and Marrow Transplantation retrospective study - Styczyński, Jan; Tridello, Gloria; Xhaard, Alienor; Medinger, Michael; Mielke, Stephan; Taskinen, Mervi; Blijlevens, Nicole; Rodriguez, M Aranzazu Bermudez; Solano, Carlos; Nikolousis, Emmanouil; Biffi, Alessandra; Groll, Andreas H; et al. (Bone marrow transplantation, 2021)
Letermovir (LMV) is licensed for prophylaxis of CMV infection in allogeneic hematopoietic cell transplant adult CMV-seropositive patients. Due to its favorable safety profile, LMV brings potential for use in other clinical situations, outside the approved indication. The objective of the study was to analyze the efficacy and safety of the use of LMV in off-label indications in EBMT centers. A total of 49 patients were reported including 44 adults and 5 children. LMV was administered for: secondary prophylaxis (37 adults, 3 children), primary prophylaxis (2 children), pre-emptive treatment (5 adults), and therapy of CMV disease (2 adults; pneumonia, colitis). Cyclosporine was concomitantly used in 26 patients. Overall, LMV was used for a median 112 days (range: 10-473). Cumulative incidence of breakthrough infections during secondary prophylaxis was 10.1% (95% CI = 3.1-21.9). Prophylactic treatment with LMV resulted in 94.9% (95% CI = 81.0-98.7), and 81.9% (95% CI = 65.7-90.9) probability of, respectively, 60 and 120-day survival without CMV infection in patients receiving secondary prophylaxis. During therapy of CMV infection/disease, probability of 60 and 120-day overall survival was 100% and 71.4% (95% CI = 25.8-92.0), respectively. No breakthrough infection occurred in children on LMV prophylaxis. Adverse events were reported in 15/49 (30.4%) patients: the most common being nausea/vomiting (22.4%). In conclusion, the efficacy of the use of LMV as secondary prophylaxis was high, and the preliminary experience with the use of LMV for the treatment of patients with refractory CMV infection/disease was positive. Our data showed that higher dose or prolonged therapy did not result in increased rate of adverse events.
Keywords: dospělí; Antiviral Agents; Communicable Diseases; acetáty; retrospektivní studie; Humans; kostní dřeň; Hematopoietic Stem Cell Transplantation; chinazoliny; infekční nemoci; Bone Marrow; transplantace hematopoetických kmenových buněk; Adult; antivirové látky; Cytomegalovirus; Off-Label Use; Quinazolines; lidé; off-label použití léčivého přípravku; Acetates; dítě; Child; Retrospective Studies